2003
DOI: 10.5271/sjweh.721
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic resonance imaging findings in respect to carpal tunnel syndrome

Abstract: The objective of this systematic review was to examine the technical and diagnostic capability of magnetic resonance imaging (MRI) to identify carpal tunnel syndrome (CTS). Two independent authors retrieved and screened the existing data and extracted the clinical and validity data adhering to predefined inclusion criteria. The MRI methods and findings were analyzed by two experienced radiologists. Disagreements were solved in consensus. The MRI findings of 373 affected wrists in 13 studies were compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0
5

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 26 publications
1
13
0
5
Order By: Relevance
“…However, no compatibility could be detected between the severity of these changes and complaints. This is in harmony with other examples reported in the literature (3,6,19,24,25).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, no compatibility could be detected between the severity of these changes and complaints. This is in harmony with other examples reported in the literature (3,6,19,24,25).…”
Section: Discussionsupporting
confidence: 92%
“…Likewise, it has been reported that MRI is capable or delivering more detailed images of the wrist anatomy in cases with partial or no recovery despite surgical intervention (3,11,19,25,28). Besides, it is known that MR is an objective and non-invasive method compared to EMG.…”
Section: Discussionmentioning
confidence: 99%
“…Its long axis is parallel to the flexor retinaculum in most cases. As it is traced distally, median nerve divides into its terminal branches and this anatomical formation can be seen in the most distal part of the carpal tunnel at the level of metacarpal bases (9,15,19).…”
Section: Introductionmentioning
confidence: 99%
“…These findings with the complement of EMG can be supportive to the diagnosis. On the other hand, MR findings depend on the comments of the radiologist as there is no parametric value differentiating normal and pathologic wrists, contrary to EMG (9,10,12,15,19). The aim of this study was to try to find parametric ratios to explain the pathophysiology of carpal tunnel syndrome using MR.…”
Section: Introductionmentioning
confidence: 99%
“…Another reason to use MRI in patients with peripheral neuropathies is the potential to serve as an adjunct in the diagnosis and management of these patients (Weis et al, 1986;Britz et al, 1996;Grant et al). A number of other studies have been published investigating the diagnostic accuracy of MRI for CTS (Pasternack et al, 2003;Kleindienst et al, 1996;Kleindienst et al, 1998;Mesgarzadeh et al, 1989b;Murphy et al;Oneson et al;Pierre-Jerome et al, 1996a;Radack et al;Soccetti et al, 1992;Timins et al, 1996). Our MRI protocols mainly focused on the assesment of morphologic anatomy of carpal tunnel and do not include functional MRI techniques.…”
Section: Discussionmentioning
confidence: 99%